General assessment of complance and typology of its disturbances in patients with organic defeat and anxiety-depressive psychopathologyc symptomatology - N. V. Krivankova (Journal of Education, Health and Sport, 2017)
The objective: to analyze the state of compliance and formulate typology of its disturbance in patients with organic anxiety and depressive disorders. The place of the research done: «RegionalClinicalPsychiatric Hospital». 102 patients have been examined. Methods: the Medical Compliance Scale and Global Assessment of Functioning Scale. The results obtained confirmed low level of compliance among patients with organic anxiety-depressive disorders. According to Medical Compliance Scale the group average index was 42,27 ± 0,40 points, and 93.7% of the patients revealed a violation of the global functioning. According to results of clinical-psychopathological research, the typology of compliance disturbance in patients with organic brain damage and depressive-anxiety spectrum of psychiatric symptoms was formulated as affective-confrontational type of violation (43.1%), associative-confrontational form (29.4%), cognitive-confrontational form (27.5%). The features of mental and behavioral response of patients with various types of violations of compliance to the treatment were established, as well.